PENCATATAN PENGADUAN MASYARAKAT TENTANG PENYIMPANGAN POLRI SESUAI KONSEP FADO - Noorleila Widiawati (Jurnal Kriminologi Indonesia, 2011)
Using FADO concept, this research focusing itself on to administration of civil complaint in Indonesia ,against police misconduct during their interaction with society. FADO (which first put forth by Seron, Pereira and Kovath in 2004) components being used were Unnecessary Use of Force, Abuse of Authority, Speaking Discourteously and Offensive Language. This research purpose is to describe types of police misconduct according to FADO that emerge on civil complaints, by using literature tracing along with depth interview. The research findings holds that not all components on FADO conception been shown on civil complaints administration in Indonesia, either by the police internal affairs department nor the National Police Commission. Components such as Speaking Discourteously and Offensive Language are difficult to identify. In doing so, the conclusion reach are the administration of civil complaint against police misconduct in Indonesia are not very thorough. There are no guidelines for categorization for type of misconduct in existence. So far the categorization of types of misconduct is being done through each operators or control board staff own interpretations.